United States Government-Supported Family Planning and Reproductive Health Outreach in the Democratic Republic of the Congo: Lessons Learned and Recommendations - Ibrahimi S; Youssouf B; Potts C; Dumouza A; Duff R; Malaba LS; Brunner B (Dove Medical Press, 2024)
Sahra Ibrahimi,1- 3 Bamba Youssouf,4 Christine Potts,1 Alexandre Dumouza,1 Rani Duff,1 Landry-Serges Malaba,1 Bettina Brunner1 1International Development Division, Abt Associates, Rockville, MD, USA; 2Department of Global Health, Denison University, Granville, OH, USA; 3Department of Family Science, School of Public Health, University of Maryland, College Park, MD, USA; 4Matchboxology, Johannesburg, Gauteng, province, South AfricaCorrespondence: Sahra Ibrahimi, Global Development Group, Abt Associates, 6130 Executive Blvd, Rockville, MD, USA, Tel +1 413-406-4401, Email ibrahimi.sahra3@gmail.comBackground: In response to limited contraception availability and a lack of knowledge about family planning (FP) in the Democratic Republic of the Congo (DRC), the United States Agency for International Development (USAID) Integrated Health Program (IHP) in the DRC has been providing FP services, including outreach programs in the DRC. Our study aims to assess the FP outreach program by understanding the participants' perception of the campaign, its impact on their behavior, and their feedback regarding the campaign. Additionally, we draw insights from lessons learned and provide recommendations.Methods: Between July and August 2022, we conducted 47 in-person participant interviews with women of reproductive age who used the outreach services provided by USAID IHP. Participants were randomly selected from Sud-Kivu, Kasai-Oriental, Haut-Katanga, and Tanganyika provinces. Consent and confidentiality were assured, and responses were recorded and transcribed in a Word document. We used Excel for data coding and analysis.Results: The campaign reached 95.7% of women interviewed; however, some participants could not recall specific message details. Most respondents (89.3%) reported that the campaign motivated them to make FP decisions and change their behaviors. While 14.8% of women reported making FP decisions independently, 85.1% reported making the decision jointly with their partners. Our analysis resulted in three emerging themes: 1) Increased FP outreach and improved perception of FP, 2) Improved perceived behavioral changes due to FP outreach, and 3) The need for program improvement by including men and providing additional information about possible FP side effects.Implications: Our study provides insights into how women receive information and whether they find it useful and share it with other women in their community. In particular, women's feedback about the FP outreach program and our recommendations can inform future policies and interventions.Keywords: DRC, family planning, reproductive health, community outreach, USAID